Profiling of the intestinal microbiota of stunted children in Semarang, Indonesia (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Susanti R, Zaenafreee I, Christijanti W, Mustikaningtyas D, Yuniastuti A. 2024. Profiling of the intestinal microbiota of stunted children in Semarang, Indonesia. Biodiversitas 25: 1337-1343. Stunting is a top global health priority. Gut microbiota profiles correlate with growth biomarkers, including stunting. This study aims to profile the intestinal microbiota of stunted children in Semarang, Indonesia. This research is an observational analytical study with a cross-sectional design, conducted on children aged 3-3.5 years with stunting and normal nutritional status in Bandarharjo Village, North Semarang District, Semarang City, Central Java Province, Indonesia. Fecal samples were collected, kept in a cooler box, and taken to the laboratory to be analyzed for pH, worm eggs, Alpha-1-Antitrypsin (AAT) levels, and microbiota profile. Microbial DNA was extracted from stool samples. The diversity and abundance of the gut microbiota were determined using the 16S rRNA V3-V4 gene marker region. The diversity and abundance of the intestinal microbiota of stunted children are smaller than those of non-stunted children. The ratio of Firmicutes/Bacteroidetes in intestinal stunting is 96.45, while in healthy, it is 26.05. The intestinal microbes of healthy children were dominated by Lactobacillus rhamnosus (30.92%) and Bifidobacterium breve (21.49%). The intestinal microbiota of stunted children is dominated by the bacterial species Blautia obeum (23.5%) and Faecalibacterium prausnitzii (19.13%). The concentration of AAT in the feces of stunted children is higher (75.49±7.68) than that of healthy children (26.73±4.48). The pH value of the feces of stunted children was higher (6.84±0.31) than that of healthy children (6.29±0.43). In conclusion, the composition of the microbiota indicates a condition of dysbiosis in intestinally stunted children. The intestines of stunted children may experience inflammation based on data on higher pH values, higher AAT levels, and deficiencies in bacterial species that benefit the host.